Die Reihe: Information über serielle Musik Vol. 1-8 - Eimert, Herbert 1897-1972; Stockhausen, Karlheinz 1928-2007 (Vienna Zürich London Universal, 1955)
Die Reihe (German pronunciation: [diː ˈʀaɪ̯ə]) was a German-language music academic journal, edited by Herbert Eimert and Karlheinz Stockhausen and published by Universal Edition (Vienna) between 1955 and 1962 (ISSN 0486-3267). An English edition was published, under the original German title, between 1957 and 1968 by the Theodore Presser Company (Bryn Mawr) in association with Universal Edition (London) (ISSN 0080-0775). A related book series titled "Bücher der Reihe" was begun, but only one title ever appeared in it, Herbert Eimert's Grundlagen der musikalischen Reihentechnik.
Band 1 "Elektronische Musik" (1955); Band 2 "Anton Webern" (1955): (1. Teil) Dokumente—Bekenntisse, (2. Teil) Erkenntnisse—Analysen; Band 3: "Musikalisches Handwerk" (1957); Band 4: "Junge Komponisten" (1958); Band 5: "Berichte—Analyse" (1957); Band 6: "Sprache und Musik" (1958); Band 7: "Form—Raum" (1960); Band 8: "Rückblicke" (1962)
Keywords: 20th Century (1901-2000); Music history; Music philosophy and esthetics; Electronic music; Technology